1974
DOI: 10.1051/rnd:19740501
|View full text |Cite
|
Sign up to set email alerts
|

Déterminisme Du Sexe Chez Tilapia Macrochir Et Tilapia Nilotica : Action De La Méthyltestostérone Dans l'ALIMENTATION Des Alevins Sur La Différenciation Sexuelle ; Proportion Des Sexes Dans La Descendance Des Mâles « Inversés »

Abstract: L'administration de méthyltestostérone à raison de 40 wg par gramme d'aliment à des alevins de T. nilotica et T. macvochir pendant deux mois à partir de la fin de l'incubation buccale par la mère, a conduit aux résultats suivants :-Chez T. nilotica, nous avons obtenu l'induction complète et fonctionnelle du sexe mâle chez tous les animaux traités. Certains d'entre eux ont fourni une descendance entièrement femelle, révélant un génotype sexuel femelle, ainsi qu'une homogamétie femelle.-Chez T. macrochir, nous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 0 publications
0
19
0
2
Order By: Relevance
“…In fact, only some species exhibit morphologically differentiated sex chromosomes [6]. In the others, male or female heterogamety was first deduced from results of back crossing individuals obtained by hormonal sex reversion [7], like in tilapias Oreochromis mossambicus [8] and O. niloticus [9], or from artificial gynogenesis like in rainbow trout Oncorynchus mykiss [10]. In tilapias belonging to the genus Oreochromis, the heterogametic sex may be either the male or the female depending on the species.…”
Section: Sexualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, only some species exhibit morphologically differentiated sex chromosomes [6]. In the others, male or female heterogamety was first deduced from results of back crossing individuals obtained by hormonal sex reversion [7], like in tilapias Oreochromis mossambicus [8] and O. niloticus [9], or from artificial gynogenesis like in rainbow trout Oncorynchus mykiss [10]. In tilapias belonging to the genus Oreochromis, the heterogametic sex may be either the male or the female depending on the species.…”
Section: Sexualitymentioning
confidence: 99%
“…This may explain why crossing homogametic males from one species with homogametic females from the other can give monosex male F1 offspring, an interesting result for tilapia fish farming since monosex male populations are expected to express a better growth rate without growing in number [11]. However, sex-ratio results from the back crosses between F1 and parent species suggest that the genetic determination system might not be so simple [9,11]. Recent data actually confirm that sex chromosomes of O. niloticus, although identified by in situ hybridation techniques, are still weakly differentiated [12,13], and that sex determining genes can be localised on other chromosomes [14].…”
Section: Sexualitymentioning
confidence: 99%
“…L'utilisation du développement gonadique se traduit par la formation de gonades à cellules germinales en nombre réduit (Takahashi et Takano, 1971 ;Okada et al, 1979 ;Yu et al, 1979), ou de gonades complètement stériles (Yoshikawa et Oguri, 1978a, b ;Laird et al, 1978 ;Jalabert et al, 1974b ; McBride, 1975 ;Goetz et al, 1979 ;Yu et al, 1979), ou encore par l'absence de toute ébauche génitale unilatérale (Takahashi, 1975b). Des androgènes (méthyltestostérone) ont surtout été utilisés chez les Salmonidés (Yamazaki, 1976 ;Simpson, 1976 ;Johnstone et al, 1979a,b ; (Yoshikawa et Oguri, 1978b), Tilapia aurea (Eckstein et Spira, 1965), le Carassin (Takahashi et Takano, 1972), la Truite (Ashby, 1957 ;Jalabert et al, 1975 ;Simpson, 1976 ;Johnstone et al, 1979a) (1969), Chan (1970), Harrington (1974,1975) Lepori (1980), et surtout Reinboth (1970,1980,1982 (Atz, 1964 ;Ohno, 1979) et une telle démonstration de la théorie hormonale n'a pas encore été apportée chez les Poissons (Hackmann et Reinboth, 1974 (Wachtel, 1977), femelle (ZW), chez les Oiseaux (Shalev et a/., 1978), chez des Reptiles (Pieau et al, 1979 ; et chez d'autres Amphibiens (Dournon et Zaborski, 1979a,b Muges (Bruslé, 1982).…”
unclassified
“…In the genus Oreochromis, both male homogamety (ZZ/WZ) and female homogamety (XX/XY) have been proposed, based on experimental sex ratios from intraspecific crosses, involving normal or sex-reversed parents (Clemens and Inslee, 1968;Jalabert et al, 1974;Guerrero, 1975;Jensen and Shelton, 1979). Experimental results have demonstrated that monosex progeny were obtained when sex-reversed fish of the homogametic sex were mated with normal fish of the same sex genotype (Clemens and Inslee, 1968 in O. mossambicus;Yamamoto, 1969 in Oryzia latipes; Jalabert et al, 1974 in O. niloticus).…”
Section: Introductionmentioning
confidence: 99%